Physical and mechanical properties of polypropylene nanocomposites (montmorillonite filled pp) - 223461 Rabiatul Manisah Mohamed (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Chemical Engineering (Polymer)) - Universiti Teknologi Malaysia, 2003